The Association Between Attachment and Posttraumatic Growth in a Sample of U.S. College Students - Morgan, Keith Alan (2014)
The purpose of this study is to examine the association between attachment and posttraumatic growth. Previous literature has suggested that securely attached individuals show more positive methods of coping with stress by activating their attachment system and facing the distress of a traumatic event. On the other hand, insecurely attached individuals display more negative methods of dealing with stress. Those with insecure attachment may avoid the distress of a traumatic event or not successfully activate the attachment system. Thus, it is expected that securely attached individuals will demonstrate higher levels of posttraumatic growth, or positive reactions to the experience of a traumatic event. In this study, 128 undergraduate and graduate students were sampled in a correlational study of attachment and posttraumatic growth. Results indicated a significant link between attachment and posttraumatic growth. Conclusions from this study add to both the posttraumatic growth and attachment literature by providing future directions in research and providing direction for future therapeutic practice and interventions